The effect of roughness element fillet radii on the heat transfer enhancement in an impingement cooling system - Son, C; Ireland, P; Gillespie, D; ASME (2005)
The combination of roughness elements with an impingement cooling systems offers an attractive means of achieving high heat transfer. Considerable care must be taken to choose the shape, size and the position of the roughness elements to maximise heat transfer and minimise pressure loss. In the last decade, many studies have been investigated the effect of changes in many of the geometric features, but little attention has been paid to the effect of the inevitable fillet. Blades and vanes are normally manufactured by casting so the fillet radius is unavoidable. The present paper investigates the effect of roughness element fillet radii on heat transfer enhancement in an impingement cooling system. Three configurations with streamwise ribs were studied. The streamwise ribs are all trapezoidal in cross section. In the three configurations the fillet radii are (1) 0mm (sharp-edged), (2) 3mm, and (3) 5mm. The extra heat transfer area of the sharp-edged, 3mm fillet and the 5mm fillet rib configurations are reported. Two-staggered arrays (a uniform and non-uniform hole diameter array) of impingement plates are used. The jets from odd numbered rows impinge between the ribs while the jets from even numbered rows impinge onto the ribs. Tests were conducted at three different mass flow rates for each configuration. The average and local jet Reynolds numbers varied between 21500 and 31500, and 17000 and 41000 respectively. The transient liquid crystal technique was used to produce detailed Nusselt number distributions and row resolved average Nusselt number levels. The heat transfer enhancement and pressure loss due to the streamwise ribs are also compared to the smooth surface impingement cooling channel. The research showed that the streamwise ribs with fillet radii produced lower Nusselt number levels than both sharp-edged ribs and impingement onto a smooth surface. Copyright © 2005 by ASME.